MobiQ: A modular Android application for collecting social interaction, repeated survey, GPS and photographic data - Suleiman Y. Yerima; Michael Loughlin; Sakir Sezer; John Moriarty; Mark McCann; Helen McAneney; Leeanne O’Hara; Mark A. Tully; Paul S. Ell; Robert Miller; Geraldine Macdonald (SoftwareX, 2018)
The MobiQ app for Android smartphones is a feature-rich application enabling a novel approach to data collection for longitudinal surveys. It combines continuous automatic background data collection with user supplied data. It can prompt users to complete questionnaires at regular intervals, and allows users to upload photographs for social research projects. The app has the capability to collect GPS location data, and calls and text frequency (excluding content) unobtrusively. The app transmits data to a secure cloud rather than storing research data on the phone, but can also store data temporarily if a data connection is unavailable; hence, MobiQ offers data security advantages over text- or web-based surveys using phones. MobiQ has been pilot tested in the field in a social science research project and is able to collect longitudinal social research data. Due to its modular and flexible design, MobiQ can easily be adapted to suit different research questions. Furthermore, its core design approach which allows for long-term power efficient data collection can be re-used outside the social sciences domain for other kinds of smartphone-based data-driven projects. Projects that have a requirement for communications-based, sensors-based, user-based data collection or any combination of these may find our code and design approach beneficial. For example, MobiQ code and architecture has been successfully adapted to build an app for a project investigating smartphone-based implicit authentication for mobile access control. Keywords: Longitudinal surveys, Android, Social interaction, GPS, Behaviour research, Social research, Smartphone-based data collection, GIS, e-research